2018
DOI: 10.3390/fermentation4020036
|View full text |Cite
|
Sign up to set email alerts
|

Citric Acid Production by Yarrowia lipolytica Yeast on Different Renewable Raw Materials

Abstract: Abstract:The world market of citric acid (CA) is one of the largest and fastest growing markets in the biotechnological industry. Microbiological processes for CA production have usually used the mycelial fungi Aspergillus niger as a producer and molasses as a carbon source. In this paper, we propose methods for CA production from renewable carbon substrates (rapeseed oil, glucose, glycerol, ethanol, glycerol-containing waste of biodiesel industry and glucose-containing aspen waste) by the mutant strain Yarrow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 28 publications
1
37
1
1
Order By: Relevance
“…Citric acid is a compound that finds numerous applications as an acidulant, flavoring agent and antioxidant within beverages and confectionery, infant formulas, the chemical and pharmaceutical industries [26,35]. Citric acid is recognized as safe, has a pleasant acid taste, and high water solubility as well as chelating and buffering properties [36].…”
Section: Introductionmentioning
confidence: 99%
“…Citric acid is a compound that finds numerous applications as an acidulant, flavoring agent and antioxidant within beverages and confectionery, infant formulas, the chemical and pharmaceutical industries [26,35]. Citric acid is recognized as safe, has a pleasant acid taste, and high water solubility as well as chelating and buffering properties [36].…”
Section: Introductionmentioning
confidence: 99%
“…The elevated yields for both biomass and citric acid when crude glycerol was used (Table 2) could have been attributed to the presence of fatty acids in crude glycerol fraction (Figure 4), which stimulated the enzymatic activity of the lipophilic yeast cells, generating a higher production of metabolites or biomass [65,66]. As Morgunov et al (2013) [65] implied, the utilization of waste glycerol for the cultivation of Y. lipolytica strain NG40/UV7 increased the citric acid formation yield with 40.63% compared with the results obtained for pure glycerol [65].…”
Section: Resultsmentioning
confidence: 99%
“…Previous study has demonstrated that during the YH transition in Y. lipolytica response to adverse conditions, the YlMHY1 gene expression dramatically increased [142]. [28,141,165] Deletion of YlMHY1 gene does not affect cell viability but results in complete inability to undergo mycelial growth, suggesting that YlMHY1 gene expression is the necessary cause for filamentation and acts as positive effectors in dimorphic transition [142]. Currently, it was demonstrated that disruption of YlMHY1 in Y. lipolytica increased intracellular oil accumulation due to the upregulation of citrate synthases, which further improved the citrate production and the followed direction of carbon flux towards the lipid biosynthesis rather than amino acid metabolism [150].…”
Section: Controlling Cell Shape By Gene Regulation Of Yeast-to-hypha mentioning
confidence: 96%
“…Furthermore, optimization of the carbon sources and cultivation conditions are correlated to the level of citric acid production. Current report revealed that high citric acid production (100–140 g/L) was obtained by feeding rapeseed oil, ethanol and raw glycerol in the fermentation with the Y. lipolytica NG40/UV5 strain .…”
Section: Y Lipolytica As the Biomanufacturing Platformmentioning
confidence: 99%